Historical framing of the Ukraine Crisis through the Great Patriotic War: Performativity, cultural consciousness and shared remembering - McGlynn, J (SAGE Publications, 2018)
Remembering in Russia is increasingly performative and actualised, as shown by the Russian government and media’s conflation of the Ukraine Crisis with the Great Patriotic War. By presenting the Great Patriotic War as a frame though which to understand events in Ukraine, the media and government guided domestic political perceptions of the contemporary crisis and encouraged participative shared remembering as a bulwark against threats to Russian national identity and historical legacies. Across several media sources, similarities in the frame’s thematic content, sequencing, and presentation demonstrated a concerted and sophisticated effort to exploit the Ukraine Crisis for identity construction. As part of these attempts, the media and government presented patriotic models for emulation, appropriating cultural memory in order to merge respect for the past with allegiance to government policy.